Application of Fe3O4/thiamine Magnetic Particles in the Removal of Methylene Blue - Tran-Nguyen, Lan; Suong Mai-Thi-Thu,; Thanh-Ty Nguyen,; Kim-Phung Ly,; Luu-Ngoc-Hanh Cao,; Tran Thi Bich Quyen,; Shella Permatasari Santoso,; Nguyen-Phuong-Dung Tran,; Nguyen Minh Nhut, (Applied Environmental Research, 2023)
Fe3O4/thiamine particles were prepared in this work via precipitation method. The synthesis method is based on the principle of precipitation of Fe3O4 particles in the presence of thiamine coating agent. Also, the potential application of Fe3O4/ thiamine in the removal of methylene blue (MB) was investigated. Several factors that affect the synthesis of Fe3O4/thiamine such as base concentration, mass ratio of FeCl2 to thiamine, reaction temperature, and reaction time were determined. Optimal conditions for preparing Fe3O4/thiamine are NH4OH concentration = 10%, mass ratio of FeCl2:thiamine = 5:1 (g g-1), reaction temperature = 30 °C, reaction time = 120 min. The average particle size of Fe3O4/thiamine is 293.7 nm while the specific surface area, pore diameter, and magnetization of the obtained Fe3O4/ thiamine particles are 57 m2 g-1, 192.67 Å, and 2.4 emu g-1, respectively. The interesting point of this work is to obtain the Fe3O4/thiamine at low temperature with less amount of NH4OH used. Furthermore, 79.08% of MB could be removed using Fe3O4/thiamine as an adsorbent, with a maximum adsorption capacity of 31.63 mg g-1 at pH of 10, a MB concentration of 50 mg L-1, and an adsorption time of 15 min. Adsorption kinetics studies showed that the pseudo-second-order model fitted the experimental data better than the pseudo-first-order and the adsorption process is physical adsorption following the Freundlich adsorption isotherm model. An adsorption mechanism of MB onto Fe3O4/thiamine was also suggested. The synthesized Fe3O4/ thiamine particles could be a potential material for treating wastewater.